Evaluating the life cycle costs of plant assets – a multidimensional view - Gram, Markus; Schroeder, Werner (Serbian Journal of Management, 2012)
This paper shows the results of the task group "Asset life cycle management" of the Austrian Scientific Maintenance and Asset Management Association (OVIA). One purpose of the research activities is to create a generic life cycle model for physical assets which includes all costs in every phase of the asset life cycle. The first step is a literature review determining the most established life cycle cost models. This is the input for discussing the completeness of such  frameworks with the participating industrial companies. A general model is deducted from existing approaches and the determined costs are evaluated with respect to priority and practical relevance. The result of the evaluation shows which costs are taken into account for investment decisions. Another outcome of the study is the verification of importance of the proposed costs for industrial companies, especially for the process industry. The derived life cycle cost framework is the basis for developing a calculation tool and subsequently, for further research in the flied of uncertainty-based methodologies for life cycle cost analyzing of physical plant assets.